The middle and later stone age crystal quartz technologies of Pomongwe Cave, Matopos (Zimbabwe) - Matembo, Joseph (My University, 2019)
The study examines the technology of crystal quartz pieces from Pomongwe Cave (PMG), Matopos, and south-western Zimbabwe. It focuses on the Middle and Later Stone Age (MSA and LSA) assemblages, which were excavated in the early 1960s by C. K Cooke and is housed at the Zimbabwe Museum of Human Sciences (ZMHS) in Harare. The research employs the chaîne opératoire approach to the study of crystal quartz technology, which follows all the stages of lithic production from the sourcing of the raw material through exploitation, use and discard patterns. It seeks to understand how the hunter-gatherers at Pomongwe (PMG hereafter) exploited this material and how they adapted their technologies to suit the physical and mechanical properties of crystal quartz through time at the site. On a broader scale, the study contributes to our understanding of the development of Modern Human Behaviours (MHBs). The results of the study show that the sourcing of the crystals was mainly from a secondary context throughout the MSA and LSA sequence. The presence and distribution of the material also varied throughout the MSA and LSA sequence, suggesting that the raw material was more prominent with the inhabitants during certain periods than others. The results through classification also show that not all collected crystals were exploited for lithic production, which raises questions as to why they were collected. The cores and blanks show that the crystals were mainly opened from the pyramid and exploited going towards the base of the crystal. The most notable change in the exploitation of crystal quartz throughout the MSA and LSA sequence at PMG is that of the reduction in the sizes of the blanks going towards the LSA.
A dissertation submitted in fulfilment of the requirements for the Degree of Master of Science in Archaeology to the Faculty of Science, University of Witwatersrand, 2019
Keywords: Quartz crystal microbalances; Electrochemistry